City of Fort Collins, Soldier Canyon, Horsetooth Estates, and Redstone Canyon - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2008)
Located in: Fort Collins office files. Larimer County Natural Resources Department Horsetooth Mountain Park Fuels Treatment Project for the City of Fort Collins, Soldier Canyon, Horsetooth Estates, and Redstone Canyon records related Colorado State Forest Service (CSFS) Colorado Forest Restoration Grant Subaward for Horsetooth Mountain Park. Includes: grant report/reimbursement request; financial summary; invoices; correspondence to include printed email; and maps.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado